Onderwijs, identiteitsontwikkeling bij jongeren en hun omgang met idealen Een studie naar het ontstaan van radicalisering in de vroege adolescentie en de rol van het onderwijs hierin - Jonkman, Harrie (2022)
This report examines how education can contribute to the prevention of radicalization and polarization of young people. The starting point was to link up with identity development in adolescence and developing social competences in education. By better to match the identity needs of young people, possible radical thoughts are steered towards positive political or social involvement. This approach has been underexposed to date in research and also insufficiently present in existing policy strategies for education